Teknologi Tepat Guna Dengan Sistem Aquaponik Upaya Pemanfaatan Lahan Terbatas di Kelurahan Rungkut Menanggal - Yeni Prasasti; Raafi Ramadhan Alamsyah; Antonius Dian Kurnianto; Noor Rizkiyah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Aquaponic cultivation is a technique that is very easy to implement in Rungkut Menanggal Village because it has narrow land. Aquaponics is an aquaculture activity that is integrated with hydroponic activities. developing two different commodities, fish and vegetables in a maintenance system in dry areas and limited land availability. Aquaponic technology is a combination of aquaculture technology with hydroponic technology in one system to optimize the function of water and space as a rearing medium. The plants will receive organic fertilizer automatically from the remaining feed and fish waste. The advantage of using aquaponic cultivation is that plant nutrients can be obtained from feces and leftover fish food that settles at the bottom of the pond, so that quality water is produced that meets standards for fish farming. The stability of dissolved oxygen in water will be obtained from a water recirculation system in the form of a shower that results in collisions with pool water. In addition, the production of plants cultivated with the aquaponic system will be better than conventional because of the availability of sufficient water and additional nutrients from fish feces and food scraps.